Web-Based Coffee Inventory Application: Case Study on One of The Coffee Shop in Sukabumi - Alifadillah Alifadillah; Haris Supriatna (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to gain insights into the inventory requirements of a coffee shop, develop and deploy a web-based application to enhance inventory management efficiency and assess the effects of this implementation on the coffee shop's operational processes. The methodology employed encompasses a blend of qualitative and quantitative techniques for data collecting, encompassing interviews, observations, and system testing. These methods are utilized to develop a comprehensive comprehension of the current inventory system and evaluate the efficacy of the recently built web application. The findings indicate that implementing the application resulted in a substantial enhancement in inventory management. This condition was achieved through the provision of real-time inventory tracking, a reduction in errors associated with manual recording, and an overall improvement in operational efficiency. The coffee shop workers responded positively to the product, highlighting its user-friendly nature and time-saving capabilities. Nevertheless, the study posits that forthcoming research should contemplate integrating elements such as predictive analytics to enhance stock management capabilities and develop a mobile iteration to augment flexibility and user-friendliness. This study provides additional evidence to reinforce the importance of implementing digital transformations in small-scale enterprises to address prevalent operational obstacles.